An evaluation of deviation from the international atomic energy agency-international commission on radiological protection proposed equation for calculation of radiation dose rate emanating from the patients with differentiated thyroid cancer undergoing radioiodine (I-131) therapy - Forough Dehkordi; Behrouz Rasuli; Ali Mahmoud-Pashazadeh (World Journal of Nuclear Medicine)
The main purpose of this study was to investigate dose rate emanating from patients treated with 131I to evaluate which of the theoretical formulas, inverse-square law (ISL) and International Atomic Energy Agency-International Commission on Radiological Protection (IAEA-ICRP) suggested equation, can provide a sufficiently close approximation of the measured dose rate. Measurements were performed based on the IAEA safety report No. 63 method at 0, 12, 24, and 48 h after administration of radioiodine at a distance of 1 m for 69 patients and for the rest of 67 patients, dose rate was measured at 2, 4, 24, and 48 h at a distance of 2 m. Results revealed that the ISL formula gained better approximation of measured dose rates than the IAEA-ICRP equation with the lesser error. The ISL formula is still more reliable than the novel method of dose calculation in the vicinity of patients. This finding reminded us the prime importance of distance as a radiation protection principle.